Intelligent Packet Delivery in Router Using Structure Optimized Neural Network - R. Deebalakshmi; V. L. Jyothi (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
The Internet itself is a worldwide network connecting millions of computers and less significant networks. Computers communicated by routers. Crucial the role of a router is to our technique of communicating and computing. Routers are situated at gateways, the spaces where two or more networks connect, and are the decisive device that keeps data flow between networks and keeps the networks connected to the Internet. When data is sent between places on one network or from one network to a second network the data is always seen and intended for to the proper place by the router. The router carries out this by using headers and routing tables to establish the best path for routing the data packets. This trim down the effectiveness of edge router only when the path engaged, it will enhanced by classification method, predictable classification methods like port based ,deep packet inspection and  statistical classification are give less precision. In this system structured optimized neural network is used for more precise organization. Classification output forwarded to router dynamically for intellectual packet delivery. The method will improve router competence by greater than before throughput and decreased latency.The Internet itself is a worldwide network connecting millions of computers and less significant networks. Computers communicated by routers. Crucial the role of a router is to our technique of communicating and computing. Routers are situated at gateways, the spaces where two or more networks connect, and are the decisive device that keeps data flow between networks and keeps the networks connected to the Internet. When data is sent between places on one network or from one network to a second network the data is always seen and intended for to the proper place by the router. The router carries out this by using headers and routing tables to establish the best path for routing the data packets. This trim down the effectiveness of edge router only when the path engaged, it will enhanced by classification method, predictable classification methods like port based ,deep packet inspection and  statistical classification are give less precision. In this system structured optimized neural network is used for more precise organization. Classification output forwarded to router dynamically for intellectual packet delivery. The method will improve router competence by greater than before throughput and decreased latency.